2008
DOI: 10.1111/j.1741-3737.2007.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

No Fun Anymore: Leisure and Marital Quality Across the Transition to Parenthood

Abstract: This study examines changes in leisure patterns across the transition to parenthood for dual-earner, working-class couples, as well as the relationship between leisure and marital quality. To this end, 147 heterosexual couples were interviewed across the transition to parenthood. Findings indicate that during the transition to parenthood, husbands and wives experience an initial decline in leisure, followed by a gradual incline after the wife's return to work. Overall, wives who reported more shared leisure pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
3
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 40 publications
(74 reference statements)
4
137
3
7
Order By: Relevance
“…The literature on the transition to parenthood has mostly focused on heterosexual parents and has addressed changes along dimensions ranging from division of labor to marital satisfaction (see Claxton & Perry-Jenkins, 2008;Cowan & Cowan, 1992). A few studies have explored the transition to parenthood for gay and lesbian parents with a majority of these focusing on lesbian mothers because of their greater prevalence (Erera, 2002).…”
Section: Transition To Parenthoodmentioning
confidence: 99%
“…The literature on the transition to parenthood has mostly focused on heterosexual parents and has addressed changes along dimensions ranging from division of labor to marital satisfaction (see Claxton & Perry-Jenkins, 2008;Cowan & Cowan, 1992). A few studies have explored the transition to parenthood for gay and lesbian parents with a majority of these focusing on lesbian mothers because of their greater prevalence (Erera, 2002).…”
Section: Transition To Parenthoodmentioning
confidence: 99%
“…The literature consistently shows that parents spend less time with one another in leisure—and more generally—than nonparents (Barnet-Verzat et al, 2010; Dew, 2009; Glorieux et al, 2011; Hill, 1988; Mansour & McKinnish, 2014; Voorpostel et al, 2009). The transition to parenthood initially reduces leisure shared with a spouse (Claxton & Perry-Jenkins, 2008) as couples’ shared time shifts from leisure as a couple to leisure as a family (Huston & Vangelisti, 1995) and to more instrumental tasks following the birth of a child (Clements & Markman, 1996; Huston, McHale, & Crouter, 1986). This research indicates that the nature of parents’ shared time is different than that of nonparents, suggesting the importance of examining couples’ shared time more broadly as opposed to leisure specifically.…”
Section: Work Parenting and Couples’ Shared Timementioning
confidence: 99%
“…Indeed, studies suggest that time with a spouse may be sacrificed to manage work and parenting demands (Bianchi, Robinson, & Milkie, 2006; Claxton & Perry-Jenkins, 2008; White 1983; Wight, Raley, & Bianchi, 2008). Paid workers have reported that time with a spouse is limited, which affects their marital relationships (Bianchi et al, 2006; Nomaguchi, Milkie, & Bianchi, 2005; Roxburgh, 2006).…”
mentioning
confidence: 99%
“…An abundant body of research concluded that the presence of children at home reduces relationship/marital happiness and satisfaction (Brown & Booth, 1996;Brown, Sanchez, Nock, & Wright, 2006;Dew & Wilcox, 2011;Doss, Rhoades, Stanley, & Markman, 2009;Glenn & McLanahan, 1982;Lawrence, Rothman, Cobb, Rothman, & Bradbury, 2008;Mitnick, Heyman, & Smith Slep, 2009;Sinning & Worner, 2010;Tai et al, 2014;Wendorf, Lucas, Imamoğlu, Weisfeld, & Weisfeld, 2011;Wiik et al, 2009). This reduction in relationship satisfaction has been attributed to the redistribution of roles and responsibilities in the household that follows the birth of a child (Claxton & Perry-Jenkins, 2008;Dew & Wilcox, 2011). This seems to be especially true for women engaged in full-time employment, who report lower levels of wellbeing compared to working fathers (Nomaguchi, Milkie, & Bianchi, 2005).…”
Section: Couple Characteristics Influencing Relationship Satisfactionmentioning
confidence: 99%